Trace element speciation in sludge: a preliminary study to assess contamination levels in the sewage network. Issue 13 (6th December 2022) - Islam, Md. Saiful; Phoungthong, Khamphe; Ismail, Zulhilmi; Othman, Ilya Khairanis; Shahid, Shamsuddin; Ishak, Daeng Siti Maimunah; Abu Bakar, Amyrhul; Kasiman, Erwan Hafizi; Ali, Mir Mohammad; Kabir, Md. Humayun; Ezewudo, Bede Izuchukwu; Idris, Abubakr M.
Abstract: The spreading of sewage sludge from wastewater treatment plants and various industries arouses the growing interest due to the contamination by trace elements. Sludges were collected from one sewage treatment plant and two industries in Dhaka City, Bangladesh to assess physicochemical parameters and total and fraction content of trace elements like Cr, Ni, Cu, As, Cd, Pb, Fe, Mn and Zn in sludges. We evaluated the bioavailability of theses metals by determining their speciation by sequential extraction, each metal being distributed among five fractions: exchangeable fraction, bound to carbonate fraction, Fe-Mn oxide bound fraction, organic matter bound fraction and residual fractions. We found that all the analyzed sludges had satisfactory properties from an agronomic quality point of view. The average concentration (mg/kg) of trace metals in sludge samples were in the following decreasing order Fe (12807) > Cr (200) > Mn (158) > Zn (132) > Cu (68.2) > Ni (42.5) > Pb (36.4) > As (35.1) > Cd (3.7). The results of the sequential extraction showed that Cr, Ni, Cu, Fe and Mn were largely associated with the residual fraction where As, Cd and Pb was dominantly associated with the exchangeable and carbonate bound fractions and Zn showed a considerable proportion in carbonate bound fraction. These results showed that regulations must take into account the bioavailability with regard to the characteristics of the agricultural soils on which sludge will be spread.